AJINIYOZ LIRIKASIDA BANDLI SHE’R SHAKLLARI - Allambergenova, N.G. (SCIENCE and SOCIETY, 2025)
In this article, the poem forms in the selected works of Ajiniyaz "Bulbilziban" are analyzed. Through the analysis of the stanza poems in the murabba’ and mukhammas genres, attention is paid to the form features of Ajiniyaz’s poems.